(untitled) (Biological Sciences - PJSIR, 1995)
Synthesis of some new 2-(N-Tos-or N-Phtaminoacyl or N-Tos- or N-Pht-dipeptidyl) amino-a-nitro-tor-a-methyl) benzothiazole derivatives has been described (11- XXIX). Some of the synthesized derivatives have been found to possess antimicrobial properties against a number of microorganisms.